ChemInform Abstract: A Mixed‐Ligand Chiral Rhodium(II) Catalyst Enables the Enantioselective Total Synthesis of Piperarborenine B. Issue 36 (August 2016) - Panish, Robert A.; Chintala, Srinivasa R.; Fox, Joseph M.
Abstract: A novel mixed‐ligand chiral rhodium(II) catalyst enables the first enantioselective total synthesis of the natural product piperarborenine B (IV).